2012
DOI: 10.1002/ajpa.22180
|View full text |Cite
|
Sign up to set email alerts
|

(Un‐)expected nocturnal activity in “Diurnal” Lemur catta supports cathemerality as one of the key adaptations of the lemurid radiation

Abstract: The ability to operate during the day and at night (i.e., cathemerality) is common among mammals but has rarely been identified in primates. Adaptive hypotheses assume that cathemerality represents a stable adaptation in primates, while nonadaptive hypotheses propose that it is the result of an evolutionary disequilibrium arising from human impacts on natural habitats. Madagascar offers a unique opportunity to study the evolution of activity patterns as there we find a monophyletic primate radiation that shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 56 publications
11
61
0
2
Order By: Relevance
“…We suggest that periods of bulky food intake by bamboo lemurs may require long periods of inactivity to digest dietary fibre. Ultimately, these data provide evidence that despite contrasting gastrointestinal morphologies and dietary adaptations among lemurid species, cathemeral activity provides Ultimate determinants of Hapalemur cathemerality 19 varying adaptive value, as different constraints appear to act simultaneously and/or in different ways depending on the habitat (Curtis and Rasmussen 2006;Donati et al 2013;Tattersall 2008). …”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…We suggest that periods of bulky food intake by bamboo lemurs may require long periods of inactivity to digest dietary fibre. Ultimately, these data provide evidence that despite contrasting gastrointestinal morphologies and dietary adaptations among lemurid species, cathemeral activity provides Ultimate determinants of Hapalemur cathemerality 19 varying adaptive value, as different constraints appear to act simultaneously and/or in different ways depending on the habitat (Curtis and Rasmussen 2006;Donati et al 2013;Tattersall 2008). …”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, our model revealed that H. meridionalis increased nocturnal activity when there was greater nocturnal luminosity (Eppley et al 2015a). This was not surprising given that moonlight has been shown to be similarly influential to most cathemeral (Charles-Dominique et al 1980;Wright 1989;Curtis et al 1999;Donati et al 2001Donati et al , 2009Donati et al , 2013Fernández- Thermoregulatory strategies appear to be common for many cathemeral non-primate mammals. High ambient temperatures have been shown to constrain diurnal activity in large herbivores, such as Przewalski horse (Equus ferus przewalskii) and eastern grey kangaroos (Macropus giganteus), thus reducing heat stress by remaining in the shade during the hot daytime and increasing nocturnal activity (Clarke et al 1995;Berger et al 1999).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations